Between Education and Memory: Health and Childhood in English-Canada, 1900-1950 - Gleason, Mona (Scientia Canadensis, 2006)
AbstractDespite contemporary concerns regarding the state of Canadian children's health, historians in Canada have yet to fully explore how conventional medical experts and educators thought about, and safeguarded, children's health. This paper explores the interplay between two sources of information regarding the provision of healthy children between 1900 and the end of the Second World War in the English Canadian context: curricular messages regarding health and illness aimed at public school children and the oral histories and autobiographies of adults who grew up in this period. Rather than simply juxtapose official health curriculum and lived memory, I argue that the two co-mingled to produce differing kinds of embodied knowledge aimed at the production and reproduction of hegemonic social values in the English Canadian setting. These values co-existed both harmoniously and uncomfortably, depending very much upon the priorities of, and socially constructed limitations placed upon, particular families in particular contexts.